Doświadczenia parametryzacji jednostek naukowych z obszaru nauk humanistycznych i społecznych 2013 – z myślą o parametryzacji 2017 - Antonowicz, Dominik; Brzeziński, Jerzy (Nauka. Biuro Upowszechniania i Promocji Nauki PAN, 2013)
The aim of the paper is evaluate the process of research evaluation (2013) within the field of humanities and social sciences in Poland. It also aspires to provide suggestions and improvements for the next round in 2017. The paper is divided into five major sections. In the first one we try to address the issue of ”research unit” bringing into the discussion and fundamental question of what criteria should be met to in order to be evaluated. The problem of both very small units and big and ‘hybrid’ departments will be explored in depth. The section number two elaborates on various aspects of groups of common assessment while the section three refers directly to categories that are distributed as the result of the evaluation. As the devil lies in details, in the last two sections we develop our view on ”do or don’t” of the evaluation process bringing a number of examples in order to illustrate ”down to the earth” solutions. The paper ends with set of our political and practical recommendations for the next round of the evaluation process.
Keywords: research evaluation; KEJN; Poland